Outbreak Investigation of Nipah Virus Disease in Kerala, India, 2018. (26th October 2018) - Arunkumar, Govindakarnavar; Chandni, Radhakrishnan; Mourya, Devendra T; Singh, Sujeet K; Sadanandan, Rajeev; Sudan, Preeti; Bhargava, Balram; ,
Abstract: Background: Nipah Virus (NiV) is a highly fatal emerging zoonotic virus and a potential threat to global health security. Here we describe the characteristics of the NiV outbreak that occurred in Kerala, India, during May–June 2018. Methods: We used real-time reverse transcription polymerase chain reaction analysis of throat swab, blood, urine, and cerebrospinal fluid specimens to detect NiV. Further, the viral genome was sequenced and subjected to phylogenetic analysis. We conducted an epidemiologic investigation to describe the outbreak and elucidate the dynamics of NiV transmission. Results: During 2–29 May 2018, 23 cases were identified, including the index case; 18 were laboratory confirmed. The lineage of the NiV responsible for this outbreak was closer to the Bangladesh lineage. The median age of cases was 45 years; the sex of 15 (65%) was male. The median incubation period was 9.5 days (range, 6–14 days). Of the 23 cases, 20 (87%) had respiratory symptoms. The case-fatality rate was 91%; 2 cases survived. Risk factors for infection included close proximity (ie, touching, feeding, or nursing a NiV-infected person), enabling exposure to droplet infection. The public health response included isolation of cases, contact tracing, and enforcement of hospital infection control practices. Conclusion: This is the first recorded NiV outbreak in South India. Early laboratory confirmation and an immediate public health response contained the outbreak. Abstract : The article describes the characteristics of the Nipah virus disease outbreak in Kerala, India, during May–June 2018 and the methods involved in the rapid detection of and public health response to the outbreak, comprehensively outlining the human-to-human transmission dynamics.